Debt management for development protection of the poor and the millennium development goals - Raffer, Kunibert 1951- (Cheltenham, UK Edward Elgar, 2010)
"T̀he problem of the debt burden and pleas for debt relief have been compared to the girl who killed both her parents and then pleaded for mercy on the grounds that she was an orphan. (It has been called the classic definition of chutzpah.) Kunibert Raffer has more sympathy for the debtors. He discusses the international debt problem in a profound way and his proposal, the Raffer proposal, is ingenious, practical and wise.'--Paul Streeten, Boston University, USA" "K̀unibert Raffer, a distinguished academic, has never confined himself to an ivory tower. Instead he has consistently used his extensive knowledge of law, history, economics and politics to argue for an end to the structural injustice of relationships between rich creditor countries and poor debtor nations. I have always admired the man and his work, and believe the ideas outlined in this book are vital if justice is to be the basis of international financial relations.'--Ann Pettifor, New Economics Foundation and Advocacy International" "This book exposes intolerable global double standards in the treatment of debtors and argues that fairness, economic efficiency and principles common to all civilized legal systems, must and can be applied to so-called d̀eveloping countries', or Southern sovereign debtors.".
"Tracing the history of Southern sovereign debts, describing the critical role of non-governmental organizations (NGOs) in enforcing improvements, and discussing technical debt issues, this book presents a solution incorporating the Millennium Development Goals (MDGs) as an appropriate form of debtor protection. Although most multilateral claims are statutorily subordinated to development needs, multilateral institutions wrongly claim preferred creditor status. They routinely violate their own statutes. Kunibert Raffer discusses grants and loans as alternative ways to finance the MDGs and development and necessary caveats on widely used debt statistics and indicators are made. The effects of the present US crisis are also discussed, making solving the never-ending debt problem particularly urgent." "With innovative and never-before discussed topics, this book will appeal to NGO employees, academics and students in development or international relations and political studies. Overseas development institutions and development co-operation ministries and departments will also find this a very useful reference tool."--BOOK JACKET.
Keywords: Debts, External -- Developing countries; Debt relief -- Developing countries